PRINSIP GERAK IJTIHADI UṢŪL FIQH DAN MAQĀṢID ASY-SYARĪ’AH - Masykur Rozi; Subaidi Subaidi (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2023)
The use of uṣūl fiqh and maqāṣid asy-syarī’ah as methods of finding and verifying law often causes them to overlap and even self-contradict. Therefore, it is necessary to understand the principle of motion, then operate them in their respective parts. This paper aims to examine the principles of motion of each and build a reciprocal relationship between them. This research is qualitative-documentative, with data collected from books and journals. This study concludes that initially, maqāṣid asy-syarī’ah adheres to the principle of motion of istinbāṭī uṣūl al-fiqh, then becomes a spinoff with the principles of philosophical, analytic, and applicable motion to apply the law. The position of maqāṣid asy-syarī’ah as a spinoff has the consequence that it becomes an independent part of the Islamic legal system